In vitro Methylation Assay to Study Protein Arginine Methylation - Bikkavilli, Rama Kamesh (J Vis Exp, 2014)
Protein arginine methylation is one of the most abundant post-translational modifications in the nucleus. Protein arginine methylation can be identified and/or determined via proteomic approaches, and/or immunoblotting with methyl-arginine specific antibodies. However, these techniques sometimes can be misleading and often provide false positive results. Most importantly, these techniques cannot provide direct evidence in support of the PRMT substrate specificity. In vitro methylation assays, on the other hand, are useful biochemical assays, which are sensitive, and consistently reveal if the identified proteins are indeed PRMT substrates. A typical in vitro methylation assay includes purified, active PRMTs, purified substrate and a radioisotope labeled methyl donor (S-adenosyl-L-[methyl-(3)H] methionine). Here we describe a step-by-step protocol to isolate catalytically active PRMT1, a ubiquitously expressed PRMT family member. The methyl transferase activities of the purified PRMT1 were later tested on Ras-GTPase activating protein binding protein 1 (G3BP1), a known PRMT substrate, in the presence of S-adenosyl-L-[methyl-(3)H] methionine as the methyl donor. This protocol can be employed not only for establishing the methylation status of novel physiological PRMT1 substrates, but also for understanding the basic mechanism of protein arginine methylation.